PENGARUH PENGHARGAAN DAN KOMPETENSI TERHADAP KINERJA MELALUI LOYALITAS KARYAWAN HOTEL BINTANG LIMA DI PEKANBARU - Husen Ernur, Muatir Muhammad; Harlen, Harlen; Sasmita, Jumiati (Jurnal Tepak Manajemen Bisnis, 2017)
Human resource is an important topic that should be discussed and alsomanaged by a company. Human resource in the application is often not align with thevision of the company. Indeed, a suistanable management resource is an importantfactor for the success of a company. Therefore, there are variety of ways to improveemployeeâs loyalty and performance results through rewarding employees andassessing competence in order to produce professional and high integrity employees.This study aims to observe the effect of reward and competence to performance throughemployee loyalty in Five Star Hotels, Pekanbaru. The study population initially were144 employees. The sample population was selected using the Slovin formula, whichonly a total of 106 employeesâ data are collected. Questionnaire were used for datacollectection, and the methods of data analysis using path analysis. The results shownthe reward and competence individualy have significant and positive impact onemployee loyalty and performance Five Star Hotel in Pekanbaru. In contrary, loyaltydoes not mediate the effect of reward and competence on employeeâs performance.